Incremental value of secretin-enhanced magnetic resonance cholangiopancreatography in detecting ductal communication in a population with high prevalence of small pancreatic cysts. Issue 4 (April 2015) - Rastegar, Neda; Matteoni-Athayde, Luciana G.; Eng, John; Takahashi, Naoki; Tamm, Eric P.; Mortele, Koenraad J.; Syngal, Sapna; Margolis, Daniel; Lennon, Anne Marie; Wolfgang, Christopher L.; Fishman, Elliot K.; Hruban, Ralph H.; et al.
Highlights: Secretin improved visualization of ductal communication of a cystic pancreatic lesion. No association between cysts and gender, ethnicity or type of high risk. Incremental value of secretin could offset the added cost and time. Abstract: Purpose: We investigated the incremental diagnostic yield of S-MRCP in a population with high prevalence of small pancreatic cysts. Methods: Standard MRCP protocol was performed with and without secretin using 1.5 T units in subjects undergoing pancreatic screening because of a strong family history of pancreatic cancer as part of the multicenter Cancer of the Pancreas Screening-3 trial (CAPS 3). All studies were reviewed prospectively by two independent readers who recorded the presence and number of pancreatic cysts, the presence of visualized ductal communication before and after secretin, and the degree of confidence in the diagnoses. Result: Of 202 individuals enrolled (mean age 56 years, 46% males), 93 (46%) had pancreatic cysts detected by MRCP, and 64 of the 93 had pre-and post-secretin MRCP images available for comparison. Data from the 128 readings show that 6 (6/128 = 4.7%) had ductal communication visualized only on the secretin studies compared to pre-secretin studies (odds ratio 1.28, p = 0.04). In addition, there was a statistically significant increase in confidence in reporting ductal communication after secretin compared to before secretin ( p < 0.0005). Conclusion: At 1.5 T MRI, the use of secretin can improve the visualization of ductal communication of cystic pancreatic lesions.